Photosynthetic Pigments in Shoots of Vaccinium corymbosum L. (Cv. Elliott) - Yavorska, Natalia; Vorobets, Natalia (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2019)
Shoots of Vaccinium corymbosum L. (Ericaceae), which introduced in Ukraine are thought to be responsible for several therapeutic properties. Acetone (80 and 100 %), ethanol (96 %), and dyethyl ether extracts were prepared from aerial parts of V. corymbosum cv. Elliott in order to examine chlorophyll a and b, and carotenoids content. The quantitative content of chlorophyll a and b, and carotenoids in the shoots of V. corymbosum of the Elliott variety has been investigated and the dynamics of their seasonal accumulation, depending on the vegetation phase, has been analyzed. The content of pigments was determined spectrophotometrically at wavelengths that correspond to the absorption maxima of chlorophylls a and b and carotenoids for each solvent. For comparison, Vaccinium uliginosum L. (bog bilberry) shoots were used, as an aboriginal European species of Ericaceae. It was established that the best solvent for extraction of chlorophylls in V. corymbosum shoots is 100 % acetone, as compared to 96 % ethanol and diethyl ether. The highest content of both chlorophylls was in the flowering and fruiting stages. The maximum values for chlorophylls a and b content were recorded in autumn period – end of September-beginning of October (phase III of growing season ): 78.57 ±2.02 mg/100 g DW for chlorophyll a, and 81.13 0.72 mg/100 g DW for chlorophyll b. In the 80% acetone as extragent the maximum values for both chlorophylls were observed in Phase II of fruiting 73.24 ±0.27 mg/100 g DW for chlorophyll a and 48.51 ±0.55 mg/100 g DW for chlorophyll b. In all the variants studied, the minimum value of chlorophylls a and b was observed in the IV winter growing season. The content of chlorophylls in the shoots of V. corymbosum is higher compared to the V. uliginosum during fruiting period, and the total content of carotenoids in the V. corymbosum and V. uliginosum shoots was not significantly different at the fruiting stage.